Expanding the Ownership Base in the Libyan Economy "A Proposed Model" - فياض, محمد (Dirasat in Economics and Business, 2007)
Most of the countries have adopted different economic policies to reconstruct their economies, in order to reform their economic status and to improve their performance. Privatization was the most important policy, which was adapted during 1980s of last century. One of the goals which were focused on within the privatization policy in Libya was expanding the ownership base. The main end of this theoretical study is to present the principle of the intellective frame of privatization as a concept, goals, tools, and comparing them with the concept of expanding the own-ership base, also to propose a model that can be used to achieve expanding the ownership base objective.